2019
DOI: 10.1002/jms.4384
|View full text |Cite
|
Sign up to set email alerts
|

A recommended and verified procedure for in situ tryptic digestion of formalin‐fixed paraffin‐embedded tissues for analysis by matrix‐assisted laser desorption/ionization imaging mass spectrometry

Abstract: Journal of MASS SPECTROMETRYThis month's Special Feature by Judd and colleagues from Vanderbilt University outlines key considerations when preparing formalin-fixed paraffin-embedded (FFPE) tissues for matrix-assisted laser desorption/ionization (MALDI) imaging mass spectrometry (MALDI IMS). MALDI IMS is a untargeted tool for imaging tissue and providing spatial information about the constituent analytes, but this powerful strategy is yet to reach its full potential. In part this is because before any research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 38 publications
(50 reference statements)
0
41
0
Order By: Relevance
“…On-tissue digestion was performed as described previously (Judd et al, 2019). Briefly, the sections were sprayed with trypsin (15 ng/µL in 10% ACN in 100 mM ammonium bicarbonate, pH 8) using a TM Sprayer (HTX Technologies, Carrboro, NC, USA) modified with a syringe pump at 8 μL/min (Harvard Apparatus, Holliston, MA, USA).…”
Section: On-tissue Digestion and Maldi Matrix Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…On-tissue digestion was performed as described previously (Judd et al, 2019). Briefly, the sections were sprayed with trypsin (15 ng/µL in 10% ACN in 100 mM ammonium bicarbonate, pH 8) using a TM Sprayer (HTX Technologies, Carrboro, NC, USA) modified with a syringe pump at 8 μL/min (Harvard Apparatus, Holliston, MA, USA).…”
Section: On-tissue Digestion and Maldi Matrix Applicationmentioning
confidence: 99%
“…In addition, soluble proteins are more favored in the MALDI process (Seeley and Caprioli, 2008); however, many important proteins are neither small nor soluble. To overcome these limitations, in situ digestion protocols were developed that typically yield peptides between 400 and 3500 Da; a range in which instrumental sensitivity is higher than that for intact proteins (Groseclose et al, 2007;Judd et al, 2019;Lemaire et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 IMS offers an untargeted mapping capability for hundreds to thousands of molecules in a single experiment. Moreover, IMS provides the analytical flexibility to investigate different classes of biomolecules including small metabolites, 13,14 lipids, 15,16 drugs, 17,18 glycans, 19,20 peptides, 21,22 and proteins. 23,24 However, IMS faces challenges of dynamic range, peak capacity, and the ability to structurally identify as defined by the Mason-Schamp equation.…”
Section: Introductionmentioning
confidence: 99%
“…After the pioneering phase, challenging technical aspects of this approach, such as the interference of hemoglobin and the stability of the samples, were overcome [4,5]. Furthermore, recent technical improvements related to the increased lateral resolution that can be achieved by MALDI-TOF-MS instrumentation enable the detection of small cell subpopulations based on their different protein profiles (i.e., profiles of single cell types), even within regions that are indistinguishable at the microscopic level, highlighting how molecular imaging can be combined with traditional pathology to generate protein signatures and build classification models [6,7,8,9]. Moreover, we have reported that MALDI-MSI is able to distinguish benign and malignant cases in different cytological thyroid specimens [1,2,3].…”
Section: Introductionmentioning
confidence: 99%